THE ATTITUDE OF DENTISTS TOWARDS THE PROVISION OF MEDICAL CARE TO ELDERLY AND SENILE PATIENTS - Токмакова, Светлана Ивановна; Луницына, Юлия Васильевна; Тимченко, Наталья Станиславовна; Бондаренко, Ольга Владимировна; Чудова, Лариса Владимировна; Гуревич, Юрий Юрьевич; Малярчук, Анастасия Янисовна (Medicine in Kuzbass, 2024)
Elderly and senile patients are an integral part of society and need qualified dental care. The formation of attitudes towards elderly patients is also a key component of the development of professional education and practical skills of medical students. The purpose of the study is to assess the willingness of dental students and doctors to provide qualified care to elderly patients. Materials and methods. With the help of the developed questionnaire, a sociological study was conducted among students of the dental institute and dentists. The respondents were asked to answer questions about the desire to develop in the field of gerontostomatology, about the main dental diseases of senile and elderly people, about the possibility of using modern methods of therapeutic and orthopedic treatment in the process of dental rehabilitation of such patients and about barriers that may arise in the process of providing care to age-related patients. Participation in the study was voluntary and informed consent was obtained. Statistical processing was carried out. Results. 136 students and 120 practicing dentists took part in the sociological survey. According to the results of the survey, respondents focus more on young and mature patients in their practical activities. Few are willing to work with age-related patients. Most are not ready to develop their knowledge and skills in the field of gerontostomatology. Among the most common problems in the oral cavity of elderly and senile patients, respondents noted: lack of teeth, lack of modern prostheses, high prevalence of non-carious lesions and periodontal diseases. The survey identified barriers to effective treatment in this category of patients: the presence of concomitant pathology that contributes to the development of complications, financial insolvency of patients, anatomical and physiological prerequisites that prevent rapid and high-quality dental care. Conclusion. The process of dental rehabilitation of elderly and senile patients is complicated due to their psychological and physiological characteristics, among which somatic pathology occupies an important place. But despite all the difficulties, given the worldwide trend of aging of the population, dentists should have the skills to treat this category of patients. When teaching students, it is necessary to pay attention to the development of the communication skills of future doctors, when forming sections of disciplines, it is necessary to include questions concerning the specifics of providing dental care to patients over 60 years of age.